Remote Control of Filchner‐Ronne Ice Shelf Melt Rates by the Antarctic Slope Current - Bull, Christopher Y. S.; Jenkins, Adrian; Jourdain, Nicolas; Vaňková, Irena; Holland, Paul R.; Mathiot, Pierre; Hausmann, Ute; Sallée, Jean-Baptiste (Journal of Geophysical Research: Oceans, 2021)
International audience Recent work on the Filchner-Ronne Ice Shelf (FRIS) system has shown that a redirection of the coastal current in the southeastern Weddell Sea could lead to a regime change in which an intrusion of warm Modified Circumpolar Deep Water results in large increases in the basal melt rate. Work to date has mostly focused on how increases in the Modified Circumpolar Deep Water crossing the continental shelf break leads directly to heat driven changes in melting in the ice-shelf cavity. In this study, we introduce a Weddell Sea regional ocean model configuration with static ice shelves. We evaluate a reference simulation against radar observations of melting, and find good agreement between the simulated and observed mean melt rates. We analyze 28 sensitivity experiments that simulate the influence of changes in remote water properties of the Antarctic Slope Current on basal melting in the FRIS. We find that remote changes in salinity quasi-linearly modulate the mean FRIS net melt rate. Changes in remote temperature quadratically vary the FRIS net melt rate. In both salinity and temperature perturbations, the response is rapid and transient, with a recovery time-scale of 5–15 years dependent on the size/type of perturbation. We show that the two types of perturbations lead to different changes on the continental shelf, and that ultimately different factors modulate the melt rates in the FRIS cavity. We discuss how these results, are relevant for ocean hindcast simulations, sea level, and melt rate projections of the FRIS.